Clinical evaluation of platelet-rich plasma and bioactive glass in the treatment of intra-bony defects - Becen Demir (Blackwell Synergy, 2007)
Background: There are limited numbers of studies focused on the using of plateletrich plasma (PRP) combined with different types of bone substitutes in intra-bony defects. Aim: The purpose of this study was to evaluate the effect of bioactive glass graft material (BG) with and without PRP on the clinical healing of intra-bony defects. Materials and Methods: Twenty-nine intra-bony defects were randomly treated with either PRP/BG or BG alone. Clinical parameters were recorded at baseline and repeated 9 months after surgery and surgical reentries were also performed. Results: The results showed that both treatment modalities were effective. Pocket depth reduction of 3.60 0.51 mm, clinical attachment gain of 3.3 1.77mm and defect fill of 3.47 0.53mm were noted in the PRP/BG group, with 3.29 1.68, 2.86 1.56 and 3.36 0.55mm improvements, respectively, noted for the BG group. None of the differences between the two treatment modalities were statistically significant. Conclusions: It is suggested that both PRP/BG combination and BG alone are effective in the treatment of intra-bony defects. The results also showed that using PRP with BG has no additional benefit in the reduction of pocket depth, clinical attachment gain and defect fill.